Chitosan Micro/Nanocapsules in Action: Linking Design, Production, and Therapeutic Application - Yaride Pérez-Pacheco; Bartosz Tylkowski; Ricard García-Valls (Molecules)
pH sensitivity of chitosan allows for precise phase transitions in acidic environments, controlling swelling and shrinking, making chitosan suitable for drug delivery systems. pH transitions are modulated by the presence of cross-linkers by the functionalization of the chitosan chain. This review relays a summary of chitosan functionalization and tailoring to optimize drug release. The potential to customize chitosan for different environments and therapeutic uses introduces opportunities for drug encapsulation and release. The focus on improving drug encapsulation and sustained release in specific tissues is an advanced interpretation, reflecting the evolving role of chitosan in achieving targeted and more efficient therapeutic outcomes. This review describes strategies to improve solubility and stability and ensure the controlled release of encapsulated drugs. The discussion on optimizing factors like cross-linking density, particle size, and pH for controlled drug release introduces a deeper understanding of how to achieve specific therapeutic effects. These strategies represent a refined approach to designing chitosan-based systems, pushing the boundaries of sustained release technologies and offering new avenues for precise drug delivery profiles.